The endoplasmic reticulum-localized Ca2+-ATPase OsACA5 regulates immunity and the seed setting rate in rice - Zhang, Min; Zhang, Yong; Peng, Zhirong; Tang, Shanjun; Zhang, Zaireng; Liu, Chenming; Luo, Xiao; Xing, Junjie (Frontiers in Plant Science, 2026)
Calcium signaling plays a central role in plant immunity and development, and its homeostasis relies on the precise regulation of calcium transporters such as Ca2+-ATPases. However, the mechanisms by which Ca2+-ATPases coordinate disease resistance and reproductive development in rice remain largely unclear. In this study, we investigated the function of the endoplasmic reticulum (ER)-localized Ca2+-ATPase gene Oryza sativa autoinhibited Ca2+-ATPase 5 (OsACA5). The expression of OsACA5 was induced by infection with the rice blast fungus Magnaporthe oryzae and by the pathogen-associated molecular pattern (PAMP) flg22. In contrast, loss-of-function osaca5 mutants exhibited significantly enhanced resistance to rice blast, as evidenced by reduced lesion areas, increased reactive oxygen species (ROS) production, and elevated expression of defense-related genes, indicating that OsACA5 acts as a negative regulator of plant immunity. Further analyses revealed that OsACA5 negatively regulates early PAMP-triggered immunity (PTI)-associated Ca2+ influx induced by flg22 and chitin, thereby suppressing immune activation. In addition to enhanced disease resistance, osaca5 mutants displayed notable agronomic changes, including reduced seed setting rate and plant height, as well as increased thousand-grain weight and grain length. Together, these findings demonstrate that OsACA5 plays a critical role in balancing disease resistance and reproductive development in rice by modulating PTI-associated calcium signaling, providing new insights into the regulatory function of ER-localized Ca2+-ATPases and offering a potential strategy for breeding rice varieties with stable disease resistance and optimized yield-related traits.